A variant of SCID with specific immune responses and predominance of γδ T cells - Stephan Ehl; Klaus Schwarz; Anselm Enders; Ulrich Duffner; Ulrich Pannicke; Joachim Kühr; Françoise Mascart; Annette Schmitt-Graeff; Charlotte Niemeyer; Paul Fisch (The Journal of Clinical Investigation, 2005)
We describe here a patient with a clinical and molecular diagnosis of recombinase activating gene 1–deficient (RAG1-deficient) SCID, who produced specific antibodies despite minimal B cell numbers. Memory B cells were detected and antibodies were produced not only against some vaccines and infections, but also against autoantigens. The patient had severely reduced levels of oligoclonal T cells expressing the αβ TCR but surprisingly normal numbers of T cells expressing the γδ TCR. Analysis at a clonal level and TCR complementarity-determining region–3 spectratyping for γδ T cells revealed a diversified oligoclonal repertoire with predominance of cells expressing a γ4-δ3 TCR. Several γδ T cell clones displayed reactivity against CMV-infected cells. These observations are compatible with 2 non–mutually exclusive explanations for the γδ T cell predominance: a developmental advantage and infection-triggered, antigen-driven peripheral expansion. The patient carried the homozygous hypomorphic R561H RAG1 mutation leading to reduced V(D)J recombination but lacked all clinical features characteristic of Omenn syndrome. This report describes a new phenotype of RAG deficiency and shows that the ability to form specific antibodies does not exclude the diagnosis of SCID.